TANTANGAN DAN KENDALA GURU DALAM MENGIMPLEMENTASIKAN SERTA MEMPERSIAPKAN MEDIA PEMBELAJARAN DI KELAS SECARA OPTIMAL - Fatikasari, Ibisanti; Sukma, Elfia; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the challenges and obstacles faced by teachers in implementing and preparing learning media in the classroom optimally. The development of information and communication technology drives the transformation of learning toward more interactive, innovative, and student-centered approaches. However, the integration of learning media in the classroom does not always run optimally due to various technical, pedagogical, and human resource limitations. This study uses a qualitative descriptive approach with data collection through observation, interview, and documentation at Grade IV of SDN 13 Kapalo Koto, Pauh District, Padang City, West Sumatera. The research subjects were Grade IV homeroom teachers selected through purposive sampling. The results show that the main challenges faced by teachers include: (1) low student discipline in using digital devices in the classroom; (2) teachers’ limited time in designing innovative and varied learning media; and (3) lack of variety in learning media use despite the availability of facilities such as laptops, LCD projectors, and speakers. Data analysis was conducted through three stages: data reduction, data presentation, and inductive conclusion drawing. This study confirms that the optimization of learning media requires synergy between teachers’ pedagogical competence, effective classroom management strategies, and adequate media variety.